Literatura e cinema: o caso de Singularidades de uma rapariga loura - Santos, Stephannie Campos Rodrigues dos [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper consists in the study of the configuration of diegetic elements which constitute the film Singularidades de uma rapariga loura (Eccentricities of a blonde-haired girl) released in 2009, produced by the portuguese moviemaker Manoel de Oliveira, in order to mention the main differences and similarities in relation to the diegetic composition of the homonym short story which Eça de Queiroz published in 1874. The comparative reading of these works which were developed in different languages - literature and cinema - offers resources to the comprehension about the aesthetic and ideological proposal of both artists. Whether Eça de Queiroz emphasizes his criticism and opposition to the Romantic period, Manoel de Oliveira criticizes the commercial cinema. This paper also consists in approach especially the irony, which is a present element in the short story and film in conjunction to the theatricality, which is another element of utmost importance present in both works. In short, this is an interdisciplinary research which involves literature and cinema as well as the narrative peculiarities from the productions in question

Este trabalho consiste no estudo da configuração dos elementos diegéticos que constituem o filme Singularidades de uma rapariga loura (2009), realizado pelo cineasta português Manoel de Oliveira (1908-2015), a fim de destacar as principais semelhanças e dissemelhanças em relação à composição diegética do conto homônimo que Eça de Queiroz deu a lume em 1874. A leitura comparada das obras que foram desenvolvidas em duas linguagens distintas - a literatura e o cinema - oferece recursos para o entendimento das propostas estéticas e ideológicas de ambos os artistas. Se Eça de Queiroz dá ênfase à critica e à oposição ao Romantismo, Manoel de Oliveira faz crítica ao cinema comercial. O trabalho também consiste em abordar, sobretudo, a ironia, elemento presente no filme e no conto em conjunto com a teatralidade, outro elemento de extrema relevância que configura ambas as obras. Em suma, trata-se de um trabalho interdisciplinar que envolve a literatura e o cinema, bem como as peculiaridades narrativas das produções em pauta
Keywords: Queiroz, Eça de 1845-1900 Singularidades de uma rapariga loura; Oliveira, Manoel de 1908-2015 Singularidades de uma rapariga loura; Literatura; Ironia; Cinema; Literature